Reflections on Responsible Tourism in the Framework of Social Responsibility - Mejia Reátiga, Camilo Antonio; Ortiz, Meylin Heleana (Cuadernos de Administración, 2020)
This reflection article presents a tour of the fundamental elements of Corporate Social Responsibility (CSR) in the context of the hotel subsector, with special emphasis on sustainability perspectives, known as triple accountability: environmental, social and economic variable. It is expected that the reader can understand from the documentary analysis of the corresponding literature, the relationship between CSR and hotel activity, as well as the relevant variables in the development of responsible practices (as regards triple accountability) of mentioned industry. In addition, this article includes an approach to the opportunities for improvement around these corporate social responsibility practices in the hotel subsector and the gap, praxeology, present between sustainable tourism (as a framework within which the hotel subsector is located) and the responsible tourism, horizon towards which the duty of the subsector is framed.